Cardiac adiposity as a modulator of cardiovascular disease in HIV. Issue 10 (12th September 2021) - Bonou, Maria; Kapelios, Chris J.; Protogerou, Athanase D.; Mavrogeni, Sophie; Aggeli, Constantina; Markousis‐Mavrogenis, George; Psichogiou, Mina; Barbetseas, John
Abstract: Background: With the number of people living with human immunodeficiency virus (HIV) steadily increasing, cardiovascular disease has emerged as a leading cause of non‐HIV related mortality. People living with HIV (PLWH) appear to be at increased risk of coronary artery disease and heart failure (HF), while the underlying mechanism appears to be multifactorial. In the general population, ectopic cardiac adiposity has been highlighted as an important modulator of accelerated coronary artery atherosclerosis, arrhythmogenesis and HF with preserved ejection fraction (HFpEF). Cardiac adiposity is also strongly linked with obesity, especially with visceral adipose tissue accumulation. Aims: This review aims to summarize the possible role of cardiac fat depositions, assessed by imaging modalities, as potential contributors to the increased cardiac morbidity and mortality seen in PLWH, as well as therapeutic targets in the current ART era. Materials & Methods: Review of contemporary literature on this topic. Discussion: Despite antiretroviral therapy (ART), PLWH have evidence of persistent, HIV‐related systemic inflammation and body fat alterations. Cardiac adiposity can play an additional role in the pathogenesis of cardiovascular disease in the HIV setting. Imaging modalities such as echocardiography, cardiac multidetector computed tomography and cardiac magnetic resonance have demonstrated increased adipose tissue. Studies show that high cardiac fat depots play an additive role in promoting coronary artery atherosclerosis and HFpEF in PLWH. Systemic inflammation due to HIV infection, metabolic adverse effects of ART, adipose alterations in the ageing HIV population, inflammation and immune activation are likely important mechanisms for adipose dysfunction and disproportionately occurrence of ectopic fat depots in the heart among PLWH. Conclusions: High cardiac adiposity seems to plays an additive role in promoting coronary artery atherosclerosis and HFpEF in PLWH. The underlying mechanisms are multiple and warrant further investigation. Improved understanding of the regulating mechanisms that increase cardiovascular risk in HIV infection may give rise to more tailored therapeutic strategies targeting cardiac fat depots.